2006
DOI: 10.1002/ajhb.20512
|View full text |Cite
|
Sign up to set email alerts
|

Asian and non‐Asian origins of Mon‐Khmer‐ and Mundari‐speaking Austro‐Asiatic populations of India

Abstract: In the present study, we analyzed 1,686 samples from 31 tribal populations of India for the mitochondrial DNA 9-base-pair deletion/insertion polymorphism, and characterized them based on the relevant mitochondrial DNA coding-region single nucleotide polymorphisms and hypervariable region I motifs, to test the genetic origins of the ethnically and linguistically heterogeneous Austro-Asiatic tribes of India. A comparative analysis of our results with the existing data suggests multiple origins of Austro-Asiatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Unfortunately, the most geographically proximal source region, Myanmar, has not been extensively characterized for mtDNA sequence variation but a survey of data from the neighboring states of Northeast India, Malaysia, Thailand, and the Yunnan province of China for mtDNA control and partial coding region data reveals no clear candidate members of M31 0 32 (Fucharoen et al, 2001;Oota et al, 2001;Cordaux et al, 2003;Metspalu et al, 2004;Wen et al, 2004;Oota et al, 2005;Wen et al, 2005;Hill et al, 2006;Kumar et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the most geographically proximal source region, Myanmar, has not been extensively characterized for mtDNA sequence variation but a survey of data from the neighboring states of Northeast India, Malaysia, Thailand, and the Yunnan province of China for mtDNA control and partial coding region data reveals no clear candidate members of M31 0 32 (Fucharoen et al, 2001;Oota et al, 2001;Cordaux et al, 2003;Metspalu et al, 2004;Wen et al, 2004;Oota et al, 2005;Wen et al, 2005;Hill et al, 2006;Kumar et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…East West Bengal 13 Roychoudhury et al 2000Roychoudhury et al , 2001Basu et al 2003;40-52 Cordaux et al 2003;Metspalu et al 2004;Thanseem et al 2006;Sun et al 2006;Rajkumar et al 2005;Kumar et al 2006. Bihar 5 Rajkumar et al 2005Thangaraj et al 2005bThangaraj et al , 2006 53-57 Orissa 15 Roychoudhury et al 2000Roychoudhury et al , 200158-72 Basu et al 2003;Cordaux et al 2003;Rajkumar et al 2005;Kumar et al 2006;Sahoo and Kashyap 2006;Thangaraj et al 2006.…”
Section: -39mentioning
confidence: 95%
“…Kivisild et al 1999Kivisild et al , 2003Basu et al 2003;3-8 Metspalu et al 2004;Thanseem et al 2006. Uttar Pradesh 10 Kivisild et al 1999Roychoudhury et al 2000;9-18 Basu et al 2003;Cordaux et al 2003;Metspalu et al 2004;Sun et al 2006;Thangaraj et al 2005b;Kumar et al 2006;Thanseem et al 2006. Roychoudhury et al 2000.…”
Section: Macrohaplogroup M In Indian Populationsmentioning
confidence: 97%
“…The study also found sharing of common mtDNA haplotype across the tribes. Kumar et al (2006) examined the mitochondrial DNA 9-bp deletion/insertion among 31 AustroAsiatic populations (Mundari and Mon-Khmer) and their results suggested multiple origins/migrations and distinctive origin of Austro-Asiatic populations; the Mundari groups (of African origin) probably being the earliest settlers. Also, Kumar et al (2007) assayed Y-STR and SNP markers among 25 AA groups and Southeast Asian populations and detected strong paternal genetic link between the Indian AA and the studied Southeast Asian populations.…”
Section: Genetic Relationship Between Tb Aa and Dr Tribesmentioning
confidence: 98%